Peran Literasi Pangan Orang Tua dalam Mencengah Stunting Pada Anak Usia Dini: A Systematic Literature Review - Nikita, Nikita; Syarifah, Erie Siti; Mustapa, Noviana; Kurniawati, Asih Budi (Institut Agama Islam Negeri Madura, 2026)
Stunting in early childhood is a major nutritional problem that impairs children’s physical growth and cognitive development. One of the main contributing factors is the low level of parental food literacy, particularly among mothers. This study systematically reviews existing literature on parental understanding of food literacy and its role in preventing stunting in early childhood. A Systematic Literature Review (SLR) was conducted using the PRISMA. Articles were retrieved from four academic databases—Scopus, Wiley Online Library, ScienceDirect, and Taylor & Francis—covering publications between 2013 and 2024. A total of twenty eligible articles were analyzed thematically. The results show that parental food literacy significantly influences children’s dietary quality, with variations determined by education, socioeconomic status, access to information, and family food culture. Moreover, everyday practices such as food selection, preparation, and serving reflect the application of food literacy, which is strongly associated with child growth outcomes. This review highlights the importance of strengthening parental food literacy through community-based education and government-supported intervention programs as strategic measures to reduce stunting prevalence.